Diagnostic Performance of Noninvasive Methods for Liver Biopsy by Fibroscan in Pediatric - Heidari, Ghobad; Motamed, Farzaneh; Heirati, Bita; Rahmani, Parisa (Journal of Child Science, 2021)
Liver biopsy is the gold standard for the diagnosis and management of various liver diseases; however, noninvasive diagnostic modalities may help prevent adverse effects of anesthesia, prolonged hospitalization, sampling error, and other serious complications, particularly in pediatric patients. The aim of this study is to compare the results of liver biopsy and fibroscan in children with chronic liver diseases. All patients presenting chronic liver disease admitted in the ward or clinic of Tehran's Children Medical Center were enrolled in the study. Required laboratory tests were performed to diagnose the disease, followed by elastography using fibroscan 402 (M-probe) Echosens machine and liver biopsy using Menghini technique. Samples were scored by using METAVIR scoring system. Thirty-two patients were reported (68.8%, female) with autoimmune hepatitis (18.8%), Wilson disease (12.5%), and glycogen storage disease (12.5%). The most common pathologic stage and fibroscan result was stage III and F0 (46.9%), respectively. Association between pathology and fibroscan results was not significant. Nonetheless, age and diagnosis, age and Fibroscan score, and pathology and liver function test were significantly associated with each other. Fibroscan cannot be used as an alternative to liver biopsy; however, it can be a useful accessory tool.
Keywords: fibroscan; liver biopsy; elastography; pediatric; Menghini technique; METAVIR scoring